2014
DOI: 10.1242/jeb.102889
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow for bone remodelling correlates with locomotion in living and extinct birds

Abstract: Nutrient arteries enter limb bones through discrete foramina on the shafts. They are required for bone remodelling in response to mechanical loading and dynamic forces imposed by locomotion. The cross-sectional area of the nutrient foramen of the femur represents an index of blood flow rate to the shaft and thus provides insight into the animal's level of activity. Morphometric data on femoral length, mass and foramen size from 100 extant bird species and eight extinct moa species were analysed allometrically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 53 publications
2
46
0
Order By: Relevance
“…During bone remodelling, bone matrices are dissolved by osteoclasts and then renewed by osteoblasts associated with capillary loops in the secondary osteons of Haversian bone (Rucci, 2008). An index of blood flow rate (Q i ), based on the size of the femoral nutrient foramina of adult mammals, reptiles and birds, appears to be proportional to locomotor activity levels and can be used as an indicator of general locomotion intensity in living and extinct species (Seymour et al, 2012;Allan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During bone remodelling, bone matrices are dissolved by osteoclasts and then renewed by osteoblasts associated with capillary loops in the secondary osteons of Haversian bone (Rucci, 2008). An index of blood flow rate (Q i ), based on the size of the femoral nutrient foramina of adult mammals, reptiles and birds, appears to be proportional to locomotor activity levels and can be used as an indicator of general locomotion intensity in living and extinct species (Seymour et al, 2012;Allan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been suggested that the rate of blood flow through the femoral nutrient artery corresponds with the locomotor activity levels of terrestrial vertebrates, previous femoral bone blood flow studies using Q i have considered only the adults of several species (Seymour et al, 2012;Allan et al, 2014). There have been no studies of femoral bone blood flow rate across ontogeny.…”
Section: Introductionmentioning
confidence: 99%
“…; Allan et al. ), there are currently no precedents for modeling and quantifying the major vessels supplying blood to the skeleton, and very little is known about the morphology of, and potential variation in, the shapes of the canals themselves. A primary objective of this study was to develop a method to quantify accurately the morphology of nutrient canals, in particular their cross‐sectional areas.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, measurements of external arterial dimensions can indicate the rate of blood flow within them. Where an artery passes through a foramen in a bone, the foramen size can be a gauge of arterial size, which is the key innovation that has allowed estimates of bone perfusion in living and extinct vertebrates (Allan et al, 2014;Seymour et al, 2012).…”
Section: Introductionmentioning
confidence: 99%